Teaching Reading Comprehension by Using Directed Reading Activity (DRA) Method to the First Year Nursing students of Universitas Muhammadiyah Gombong - As’ad, Muhammad; Garwan, Hellaisna Nur’aini (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
This study was about Using Directed Reading Activity (DRA) Method to Teach ReadingComprehension to the First Year Nursing Students of Universitas MuhammadiyahGombong. The problem statements of this research were (1). What is a directed readingactivity method? (2). To what extent is the DRA method able to improve the students’ability in reading comprehension? The objective of this research was to find out whetheror not the DRA method can stimulate the students’ ability in learning readingcomprehension to the first-year Nursing students of Universitas MuhammadiyahGombong. The method applied in this research was an experiment. The sample of thisresearch consisted of 40 students to the first-year students of Universitas Muhammadiyah Gombong. The writers used purposive sampling in this research. They used a reading test that was administered in the pre-test and posttest, and used aquestionnaire as well. The result of this research showed that the first-year students ofUniversitas Muhammadiyah Gombong had an inadequate score in the pre-test. However, after doing the treatment by using the DRA method their reading comprehension got ahigh score in post-test. The data was analyzed by using a t-test and the result shows thatthe t-test value (3, 5), was greater than the t-table value (1,703). It can be concluded thatthe use of the DRA method is very effective to teach reading comprehension.